The Effect of Underwriter Reputation, Firm Size, Financial Leverage, and Profitability on IPO Underpricing in the Indonesian Stock Exchange during 2021–2024 - Shelmara Nabila Zakiyyatun Nafsi; Shinta Heru Satoto (FEB-Telkom University Publisher, 2026)
This study aims to analyze the effect of underwriter reputation, firm size, financial leverage, and profitability on the level of underpricing in companies conducting Initial Public Offerings (IPOs) on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research employs a quantitative approach using multiple linear regression analysis. The sample was selected through purposive sampling based on IPO firms with complete prospectus and financial data. The results indicate that underwriter reputation and financial leverage have a positive and significant effect on underpricing, while firm size has a negative and significant effect. Meanwhile, profitability does not have a significant effect on underpricing. These findings suggest that the reputation of underwriting institutions and the company’s capital structure play a more dominant role in determining IPO underpricing than profitability performance. This study provides insights for investors in assessing IPO stock prospects and contributes to the literature on IPO pricing behavior in emerging markets